PERAN MEDIA LEMBAR BALIK DALAM MENINGKATKAN PERILAKU IBU DALAM KESEHATAN GIGI DAN MULUT BALITA YANG DIEVALUASI MELALUI KMGS DI POSYANDU JORONG AMPANG GADANG KEC. AMPEK ANGKEK KABUPATEN AGAM TAHUN 2019 - Zulfikri Zulfikri; Lisnayetty Lisnayetty (Ensiklopedia of Journal, 2020)
Mother is a key person in the maintenance of toddler dental and oral health, high def-t and poor dental hygiene in toddlers is caused by a lack of maternal knowledge about dental and oral health, the use of flipchart media in counseling to explain about oral and dental health toddler. The purpose of this study was to determine the role of flipchart media in improving maternal behavior in the oral health of children under five who were evaluated through KMGS in Posyandu Jorong Ampang Gadang Kec. Ampek Angkek Agam Regency in 2019. This research is a cross- sectional study with a before-and-after-test design ". By measuring before and after the intervention. Samples were taken by "purposive sampling" technique, the way data was collected by filling KMGS, the data were analyzed by t-test statistical tests. Comparative test results in the control group and intervention group by looking at the results of the mother's knowledge test before and after receiving treatment, with the results of p value